Efficacy and Safety of Nilotinib (NIL) vs Imatinib (IM) in Patients (pts) With Newly Diagnosed Chronic Myeloid Leukemia in Chronic Phase (CML-CP): Long-Term Follow-Up (f/u) of ENESTnd - Richard A. Larson; Dong-Wook Kim; Surapol Issaragrilsil; Philipp le Coutre; Pedro Enrique Dorlhiac Llacer; Gabriel Etienne; Richard E. Clark; Ian Flinn; Hirohisa Nakamae; Andreas Hochhaus; Giuseppe Saglio; Hagop M. Kantarjian; et al. (Blood, 2014)
Abstract Introduction In Evaluating NIL Efficacy and Safety in Clinical Trials–Newly Diagnosed Patients (ENESTnd), frontline NIL has consistently demonstrated good tolerability and improved efficacy vs IM, with faster and higher rates of major molecular response (MMR; BCR-ABL level on the International Scale [BCR-ABLIS] ≤ 0.1%) and MR4.5 (BCR-ABLIS ≤ 0.0032%), higher probability of achieving early molecular response (EMR; BCR-ABLIS ≤ 10% at 3 mo), and reduced risk of progression to accelerated phase/blast crisis (AP/BC). Here we report 5-y f/u data; 6-y f/u data will be presented. Methods Adults with newly diagnosed Philadelphia chromosome–positive CML-CP were randomized to NIL 300 mg twice daily (BID; n = 282), NIL 400 mg BID (n = 281), or IM 400 mg once daily (QD; n = 283). Progression to AP/BC and survival were monitored prospectively, including after treatment discontinuation. Response rates and time-to-event variables were compared between groups using Cochran-Mantel-Haenszel and log-rank tests, respectively, both stratified by Sokal risk group. Nominal P values are provided for descriptive purposes only and were not adjusted for multiple comparisons. Results With 5-y minimum f/u, 60%, 62%, and 50% of pts in the NIL 300 mg BID, NIL 400 mg BID, and IM arms, respectively, remained on core treatment. Cumulative rates of MMR and MR4.5 by 5 y were higher in both NIL arms vs the IM arm (Table). Cumulative rates of MMR are unlikely to change with longer f/u because, among pts without MMR by 5 y, few remained on core treatment at data cutoff (5, 9, and 10 pts in the NIL 300 mg BID, NIL 400 mg BID, and IM arms, respectively). The difference in cumulative rates of MR4.5 between the NIL arms and IM arm increased over time (6%-10% by 1 y; 21%-23% by 5 y). There were fewer progressions to AP/BC with NIL 300 mg BID and NIL 400 mg BID vs IM, both on core treatment (n = 2 and 3 vs 12; P = .0059 and .0185) and on study (n = 10 and 6 vs 21; P = .0403 and .0028). Among pts who remained on study treatment, no pt progressed to AP/BC since the 2-y data cutoff. Among pts who discontinued from the study early, 3 had new progressions to AP/BC reported since the 4-y data cutoff (1, NIL 300 mg BID; 2, IM); all 3 had high Sokal risk at baseline and BCR-ABLIS > 10% at 3 mo. No pt who achieved MR4.5 progressed to AP/BC. There were more any-cause deaths and deaths due to advanced CML on study, respectively, in the IM arm (n = 22 and 16) than each NIL arm (300 mg BID, n = 18 and 6; 400 mg BID, n = 10 and 4). NIL resulted in better MR vs IM across all Sokal risk groups, including higher rates of EMR and MR4.5 by 5 y. Safety profiles of NIL and IM were similar to those previously reported. The frequency of cardiovascular events (CVEs) remained higher in NIL- vs IM-treated pts; more pts in the NIL 400 mg BID arm than the NIL 300 mg BID arm had CVEs. Since the 4-y data cutoff, few pts reported newly occurring or worsening grade 3/4 biochemical abnormalities (elevated lipase: 3 pts [1, NIL 300 mg BID; 2, NIL 400 mg BID]; elevated glucose: 5 pts [2, NIL 300 mg BID; 3, NIL 400 mg BID]; elevated bilirubin: 1 pt [NIL 400 mg BID]). Conclusions NIL resulted in improved efficacy vs IM, including fewer progressions and deaths due to advanced CML, and was well tolerated in most pts. Across all Sokal risk groups, NIL resulted in higher rates of deep MR, a key entry criterion for treatment-free remission studies. With long-term f/u, NIL 300 mg BID continues to show a positive benefit-risk profile in pts with newly diagnosed CML-CP. Table 1. By 5 y NIL 300 mg BID(n = 282) NIL 400 mg BID(n = 281) IM 400 mg QD(n = 283) Still in f/u, %a 86 87 83 Still on core treatment, % 60 62 50 MMR, % (P vs IM) 77 (< .0001) 77 (< .0001) 60 MR4.5, % (P vs IM) 54 (< .0001) 52 (< .0001) 31 EMR by Sokal risk score, n/N (%)b Low 90/97 (93) 93/98 (95) 81/102 (79) Intermediate 84/91 (92) 80/90 (89) 64/92 (70) High 60/70 (86) 59/72 (82) 31/70 (44) MR4.5 by Sokal risk score, n/N (%)c Low 55/103 (53) 64/103 (62) 38/104 (37) Intermediate 61/101 (60) 50/100 (50) 33/101 (33) High 35/78 (45) 33/78 (42) 18/78 (23) Selected nonhematologic adverse events and biochemical abnormalities of any grade, % Rash 38 45 19 Headache 32 36 23 Nausea 22 31 41 Diarrhea 19 23 46 Muscle spasms 12 12 34 CVEsd 8 13 2 Glucose ↑ 50 53 31 Total cholesterol ↑ 28 27 4 a Includes all pts still on core treatment or in f/u after discontinuation of core treatment. b N = pts with evaluable baseline and 3-mo BCR-ABL levels. c N = total pts in the indicated Sokal risk group. d Defined as ischemic heart disease, ischemic cerebrovascular events, or peripheral artery disease. Disclosures Larson: Novartis: Consultancy, Research Funding. Kim:Novartis: Consultancy, Honoraria, Research Funding, Speakers Bureau; BMS: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Pfizer: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Il-Yang: Consultancy, Honoraria, Research Funding. le Coutre:Novartis: Honoraria, Research Funding; BMS: Honoraria; Pfizer: Honoraria; Ariad: Honoraria. Etienne:Novartis: Consultancy, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; BMS: Consultancy, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Pfizer: Membership on an entity's Board of Directors or advisory committees; ARIAD: Membership on an entity's Board of Directors or advisory committees. Clark:Novartis Pharmaceuticals Corporation: Honoraria, Research Funding, Speakers Bureau; Bristol Myers Squibb: Honoraria, Research Funding; Pfizer: Honoraria, Research Funding. Flinn:Novartis: Research Funding. Nakamae:Novartis: Honoraria, Research Funding, Speakers Bureau, Travel/accomidations/meeting expenses Other. Hochhaus:Novartis: Honoraria, Research Funding; BMS: Honoraria, Research Funding; ARAID: Honoraria, Research Funding; Pfizer: Honoraria. Saglio:BMS: Consultancy, Fees for occasional speeches Other; Novartis: Consultancy, Fees for occasional speeches, Fees for occasional speeches Other; Pfizer: Consultancy, Fees for occasional speeches, Fees for occasional speeches Other; ARIAD: Consultancy, Fees for occasional speeches, Fees for occasional speeches Other. Kantarjian:Novartis: Research Funding. Donohue:Novartis: Employment. Deng:Novartis: Employment. Menssen:Novartis AG: Employment. Hughes:Novartis: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding; BMS: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding; Ariad: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding.